2020
DOI: 10.3389/fendo.2020.00324
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Diglycidyl Ether (BADGE) and Bisphenol Analogs, but Not Bisphenol A (BPA), Activate the CatSper Ca2+ Channel in Human Sperm

Abstract: Aim: Evidence suggests that bisphenol A diglycidyl ether (BADGE), bisphenol A (BPA), and BPA analogs can interfere with human male fertility. However, the effect directly on human sperm function is not known. The CatSper Ca 2+ channel in human sperm controls important sperm functions and is necessary for normal male fertility. Environmental chemicals have been shown to activate CatSper and thereby affect Ca 2+ signaling in human sperm. BPA has previously been investigated for effects on Ca 2+ signaling human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…In line with this, the very large Ca 2+ signal induced by the Ca 2+ -ionophores ionomycin ( Figure 1 ) and A23187 ( Figure 2 ) indicates that, at the moment of adding the ionophones to the sperm cells, a large proportion of the sperm cells must have been viable, as unviable sperm cells cannot maintain their Ca 2+ gradient across the cell membrane. Our findings therefore do not support our hypothesis that exposure of boar sperm cells to BADGE leads to reproductive failure in sows ( Nerin et al, 2014 ) through an effect on Ca 2+ signaling in boar sperm cells, similar to the effect that we have recently shown for BADGE on human sperm cells ( Rehfeld et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with this, the very large Ca 2+ signal induced by the Ca 2+ -ionophores ionomycin ( Figure 1 ) and A23187 ( Figure 2 ) indicates that, at the moment of adding the ionophones to the sperm cells, a large proportion of the sperm cells must have been viable, as unviable sperm cells cannot maintain their Ca 2+ gradient across the cell membrane. Our findings therefore do not support our hypothesis that exposure of boar sperm cells to BADGE leads to reproductive failure in sows ( Nerin et al, 2014 ) through an effect on Ca 2+ signaling in boar sperm cells, similar to the effect that we have recently shown for BADGE on human sperm cells ( Rehfeld et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Intriguingly, no effects were found on routine boar sperm parameters, including motility and viability, or on in vitro fertilization tests, but only on in vivo fertility rates in sows ( Nerin et al, 2014 ). We speculated that the reproductive failure could be due to effects on Ca 2+ signaling through an action on CatSper in the boar sperm cells, as CatSper has been shown to be expressed in boar sperm cells ( Song et al, 2011 ; Vicente-Carrillo et al, 2017 ), has been suggested to be functional through the use of CatSper-inhibitors ( Vicente-Carrillo et al, 2017 ; Machado et al, 2019 ), and as we have recently found that BADGE in μM concentrations can interfere with Ca 2+ signaling through an action on CatSper in human sperm cells ( Rehfeld et al, 2020 ). Our results here, however, showed that addition of the exact same solutions of BADGE to the sperm cells, induced transient biphasic Ca 2+ signals in the human sperm cells, but failed to do so both in non-capacitated and capacitated boar sperm cells ( n ≥ 3) ( Figure 1 ), similar to after addition of 5 μM progesterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these chemicals also have the ability to disturb gene expression, such as Kiss1 and CYP19A1, which are involved in the HPG axis and steroidogenesis, respectively [ 63 ]. Recently, the effects of BPA and its analogues on these three significant pathways, in the form of the HPG axis [ 56 , 59 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], steroidogenesis [ 55 , 56 , 59 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 74 , 75 , 76 , 77 , 78 , 79 ], and spermatogenesis outcomes [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 75 , 76 , 77 , 80 , 81 , 82 , 83 , 84 , 85 ]...…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the present study could help to understand the interaction of potentially toxic compounds with spermatozoa, as seen by other authors 25,26 . For example, in human sperm, BADGE may lead to an activation of specific Ca 2+ channels (CatSper) 27 that could influence important sperm functions.…”
Section: Discussionmentioning
confidence: 99%